2012
DOI: 10.1521/pedi_2012_26_066
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Personality Traits and Substance Use: Genetic Factors Underlie the Association with Smoking and Ever Use of Cannabis, but Not with High Alcohol Consumption

Abstract: Borderline personality disorder (BPD) and substance use disorders often co-occur. Both disorders are heritable and family studies showed that there are familial factors that increase the risk for BPD as well as substance use/abuse. This is the first study that investigates whether the association of borderline personality traits (BPT) with substance use reflects an underlying genetic vulnerability or nongenetic familial influences. To this end we analyzed data of 5,638 Dutch and Belgian twins aged between 21-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Thus, the pattern of familial aggregation of BPD across different types of relatives indicates that genetic factors play a significant role in the risk of developing BPD, and explain the familial clustering of the disorder. Previous heritability estimates vary widely [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and our results represent a substantial improvement in precision, based on our sample size and the number of BPD-diagnosed individuals, as reflected in the narrow confidence intervals for the heritability estimates. Furthermore, our findings indicate that close family members of individuals represent an important high-risk group for developing BPD; and that this is due to genetic, and not environmental, influences.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Thus, the pattern of familial aggregation of BPD across different types of relatives indicates that genetic factors play a significant role in the risk of developing BPD, and explain the familial clustering of the disorder. Previous heritability estimates vary widely [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and our results represent a substantial improvement in precision, based on our sample size and the number of BPD-diagnosed individuals, as reflected in the narrow confidence intervals for the heritability estimates. Furthermore, our findings indicate that close family members of individuals represent an important high-risk group for developing BPD; and that this is due to genetic, and not environmental, influences.…”
Section: Discussionmentioning
confidence: 48%
“…This study has several important strengths including utilizing Swedish nationwide register linkages. Previous studies are often limited by small sample sizes [7-10, 13-16, 19, 34, 36] the use of BPD-traits rather than diagnosis [7, 9, 10, 19-24, 28, 29, 31-33, 35-37, 64], and selfrating questionnaires [16,19,[21][22][23][24][25][26][27][28]30] rather than clinical diagnoses, exposing them to risks of low statistical power, selection-and recall bias. This register-based population cohort provided large sample-size, wellidentified biological relatives, extensive follow-up time, and clinical diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are unaware of any study that has jointly analysed all ten PDs to identify which PDs are most strongly linked to CU and CUD within a genetic framework. Among the genetic studies linking PDs to CU and CUD, most have focused on single PDs such as Borderline (17), or Antisocial (18). We addressed this gap with two specific aims.…”
Section: Introductionmentioning
confidence: 99%
“…Research literature indicates impulsiveness as shared personality vulnerability for bipolar spectrum status in adult individuals (Alloy et al, 2009). Regular smoking also correlated with borderline personality disorder, that correlation being explained by common genetic factors (Distel et al, 2012). This study showed that nonsmokers were much stronger in X-emotive responses than daily smokers and a statistically significant difference was found in favor of nonsmoker students.…”
Section: Discussionmentioning
confidence: 51%